Comparison of Screw Quantity and Placement of Metacarpal Fracture Fixation: A Biomechanical Study. (September 2022) - Canton, Stephen P.; Dadi, Srujan; Anthony, Austin; Black, Ryan T.; Clancy, Michael; Fowler, John R.
Background: It is recommended to have 6 bicortical screws for plate fixation of long bone fractures; however, many metacarpal fractures do not allow 6 screws due to size limitations and proximity of crucial anatomical structures. The purpose of this biomechanical study was to determine whether the mechanical properties of a 4-screw nonlocking construct are noninferior to those of a 6-screw nonlocking construct. Methods: Metacarpal sawbones were used to simulate a midshaft, transverse fracture. Nonlocking bicortical screws were placed in the 6-hole plate, and the metacarpals were randomly assigned to 2 equal study groups: (1) 4 screws, 2 on either side of the fracture (4S); and (2) 6 screws, 3 on either side of the fracture (6S). The metacarpals were tested in a cyclic loading mode and load to failure in a cantilever bending mode. Results: Maximum deflection was significantly higher for 4S compared with 6S. Cyclic root mean square (RMS) was also significantly greater for 4S at 70 and 100 N. There were no statistically significant differences observed between the 2 constructs for maximum bending load, bending stiffness, and cyclic RMS at 40 N. The maximum bending load in 4S and 6S was 245.6 ± 37.9 N and 230.8 ± 41.9 N, respectively; 4S was noninferior and not superior to 6S. Noninferiority testing was inconclusive for bending stiffness. Conclusions: A 4-screw bicortical nonlocking construct is noninferior to a 6-screw bicortical nonlocking construct for fixation of metacarpal fractures, which may be advantageous to minimize disruption of soft tissues while maintaining sufficient construct stability.